2022
DOI: 10.3390/jcm11195736
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus—Recent Literature Review

Abstract: Gestational diabetes mellitus (GDM), which is defined as a state of hyperglycemia that is first recognized during pregnancy, is currently the most common medical complication in pregnancy. GDM affects approximately 15% of pregnancies worldwide, accounting for approximately 18 million births annually. Mothers with GDM are at risk of developing gestational hypertension, pre-eclampsia and termination of pregnancy via Caesarean section. In addition, GDM increases the risk of complications, including cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 116 publications
0
36
0
5
Order By: Relevance
“…GDM and GTD represent the most prevalent endocrinopathies during pregnancy [3,4]. Taking into account the diversified screening approach and given the different risk according to ethnicity and body mass index (BMI), the prevalence of GDM ranges between 1 and 28% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…GDM and GTD represent the most prevalent endocrinopathies during pregnancy [3,4]. Taking into account the diversified screening approach and given the different risk according to ethnicity and body mass index (BMI), the prevalence of GDM ranges between 1 and 28% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to that during normal pregnancies, the incidence of complications in the third trimester among patients with GDM is significantly higher, resulting in more adverse effects with regard to maternal and infant health. Data in the literature have shown that the risk of adverse pregnancy outcomes among patients with GDM is related to maternal glycemic level[ 20 ]. The three GDM subtypes all exhibit different characteristics in terms of maternal glycemic control, and thus their adverse pregnancy risks are also different.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is defined as a disorder of glucose metabolism recognized for the first time during pregnancy, even though the abnormalities may have existed before pregnancy and may persist after the delivery [ 1 ]. It has been estimated that approximately 7% of all pregnancies are complicated by GDM, resulting in more than 200,000 worldwide cases annually [ 2 , 3 ]. The prevalence may vary from 1% to 14% of all pregnancies depending on the population studied and the diagnostic tests used [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that approximately 7% of all pregnancies are complicated by GDM, resulting in more than 200,000 worldwide cases annually [ 2 , 3 ]. The prevalence may vary from 1% to 14% of all pregnancies depending on the population studied and the diagnostic tests used [ 2 ]. GDM is the most common cause of hyperglycemia during pregnancy, accounting for more than 85% of all cases [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%